Molecular epidemiology of leprosy: an update - Avanzi, Charlotte, author; Singh, Pushpendra, author; Truman, Richard W, author; Suffys, Philip N, author (Colorado State University. Libraries, 2020)
Molecular epidemiology investigations are notoriously challenging in the leprosy field mainly because the inherent characteristics of the disease as well as its yet uncultivated causative agents, Mycobacterium leprae and M. lepromatosis. Despite significant developments in understanding the biology of leprosy bacilli through genomic approaches, the exact mechanisms of transmission is still unclear and the factors underlying pathological variation of the disease in different patients remain as major gaps in our knowledge about leprosy. Despite these difficulties, the last two decades have seen the development of genotyping procedures based on PCR-sequencing of target loci as well as by the genome-wide analysis of an increasing number of geographically diverse isolates of leprosy bacilli. This has provided a foundation for molecular epidemiology studies that are bringing a better understanding of strain evolution associated with ancient human migrations, and phylogeographical insights about the spread of disease globally. This review discusses the advantages and drawbacks of the main tools available for molecular epidemiological investigations of leprosy and summarizes various methods ranging from PCR-based genotyping to genome-typing techniques. We also describe their main applications in analyzing the short-range and long-range transmission of the disease. Finally, we summarise the current gaps and challenges that remain in the field of molecular epidemiology of leprosy.
This pre-print paper was published in Infection Genetic and evolution but is not open access (https://www.sciencedirect.com/science/article/pii/S1567134820304123?via%3Dihub#ks0005).
ZIP file includes XLSX spreadsheet.
Keywords: leprosy; molecular epidemiology; transmission; phylogeny; non-human reservoir; drug resistance